1995
DOI: 10.1021/j100036a037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 4-carboxybenzophenone-sensitized photooxidation of methionine-containing dipeptides and tripeptides in aqueous solution

Abstract: The mechanism of 4-carboxybenzophenone (CB)-sensitized photooxidation of methionine-containing dipeptides (Met-Gly and Gly-Met) and tripeptides (Met-Gly-Gly, Gly-Met-Gly, and Gly-Gly-Met) was investigated using nanosecond flash photolysis and steady-state photolysis. The rate constants for quenching of the CB triplet by sulfur-containing peptides were determined to be in the range (1.8-2.3) x lo9 M-' s-l for neutral and alkaline solutions. The presence of the various electron-transfer intermediates accompanyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…This photoactivated intermediate may then be rapidly and selectively quenched by a charge transfer complex (60) with a side chain of a Met residue within 3-6 Å (19,59) in the target to produce a covalent bond between the ligand and the target. The electron transfer quench is more than 10 4 -fold quicker for Met than toward other residues such as Ala for example; it results in an increased incorporation yield of the Bpa photoprobe into Met residues (61,62). Hence, the charge transfer complex accounts for the strong photochemical selectivity to Met of the Bpa photoprobe.…”
Section: Methodsmentioning
confidence: 99%
“…This photoactivated intermediate may then be rapidly and selectively quenched by a charge transfer complex (60) with a side chain of a Met residue within 3-6 Å (19,59) in the target to produce a covalent bond between the ligand and the target. The electron transfer quench is more than 10 4 -fold quicker for Met than toward other residues such as Ala for example; it results in an increased incorporation yield of the Bpa photoprobe into Met residues (61,62). Hence, the charge transfer complex accounts for the strong photochemical selectivity to Met of the Bpa photoprobe.…”
Section: Methodsmentioning
confidence: 99%
“…17 Preliminary work showed that by using spectral resolutions at selected time delays after the laser pulse it was possible to extract the spectrum and hence the concentration of the (S∴N) + species. 17,22 This seemed to indicate that the decay pattern of the (S∴N) + was a complex function of the pH. The current work is an attempt to unravel both the time and spectral resolution of the (S∴N) + species.…”
Section: Introductionmentioning
confidence: 99%
“…Met is symbolized by its thioether function >S. The excited triplet state of CB forms a short‐lived radical ion pair, CB .− •••>S .+ (charge‐transfer complex) with the sulfur atom (CT‐S) or with nitrogen (CT‐N). The electron transfer may occur from either the sulphur or the nitrogen atom of the quencher molecule, in this case, Met‐containing derivatives 15. This radical pair undergoes further reactions: 1) back electron transfer to the substrates; 2) proton transfer with the formation of CBH .…”
Section: Sensitized Photolysismentioning
confidence: 99%